Teachers' Perspectives on the Implementation of Inclusive Education Services for Children with Special Needs (ABK) in Indonesia: A Literature Review - Ulya, Rifqi Minchatul; Hendriani, Wiwin (IAIN Kudus, 2023)
Teachers' Perspectives on the Implementation of Inclusive Education Services for Children with Special Needs (ABK) in Indonesia: A Literature Review. Perspective is a certain point of view, way of thinking, and attitude about something, the ability to understand or interpret a comprehensive phenomenon in a way that makes sense, in this study, namely the implementation of inclusive education services for children with special needs. This study aims to find out teachers' perspectives on the implementation of inclusive education services for children with disabilities in various parts of Indonesia. The research method used was a systematic literature review using articles obtained online from three databases, namely google scholar, science direct, and Garuda portal with a limit of publishing the last five years. Six articles met the criteria and the results of this systematic literature review showed that in general, teachers' perspectives are positive toward the implementation of inclusive education for children with disabilities, however, it has not been maximized because there are not many adequate human resources so it is necessary to increase the capacity of educators to improve the quality of inclusive education in Indonesia.Keywords: Teachers' Perspectives, Inclusive Education, Special Needs